2020
DOI: 10.1186/s12870-020-02771-z
|View full text |Cite
|
Sign up to set email alerts
|

Genome-wide identification and expression analysis of the CLC gene family in pomegranate (Punica granatum) reveals its roles in salt resistance

Abstract: Backgrounds Pomegranate (Punica granatum L.) is an important commercial fruit tree, with moderate tolerance to salinity. The balance of Cl− and other anions in pomegranate tissues are affected by salinity, however, the accumulation patterns of anions are poorly understood. The chloride channel (CLC) gene family is involved in conducting Cl−, NO3−, HCO3− and I−, but its characteristics have not been reported on pomegranate. Results In this study, we… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(15 citation statements)
references
References 64 publications
3
12
0
Order By: Relevance
“…RNA-Seq data demonstrated that three genes were enriched after ABA treatment and seven after the application of diniconazole. Similar results have been previously observed in Dendrobium officinale 52 and Poa pratensis 53 exposed to abiotic stress conditions. These results indicate that WR04-6 can respond to ABA by actively regulating glycolysis and TCA cycle pathway-related genes and enzyme activities.…”
Section: Discussionsupporting
confidence: 91%
“…RNA-Seq data demonstrated that three genes were enriched after ABA treatment and seven after the application of diniconazole. Similar results have been previously observed in Dendrobium officinale 52 and Poa pratensis 53 exposed to abiotic stress conditions. These results indicate that WR04-6 can respond to ABA by actively regulating glycolysis and TCA cycle pathway-related genes and enzyme activities.…”
Section: Discussionsupporting
confidence: 91%
“…In pomegranate ( Punica granatum ), the expression level of the PgCLC genes under salt stress was high in leaves and low in roots. Moreover, PgCLC genes have been shown to affect the accumulation of Cl − , SO 4 2− , and NO 3 − in pomegranate tissues under salt stress ( Liu C. et al, 2020 ). Our results showed that all TaCLC genes were expressed under low nitrogen stress conditions over the short term.…”
Section: Discussionmentioning
confidence: 99%
“…Later, it was discovered that the CLC family genes also existed in most plants, including Arabidopsis thaliana , Nicotiana tabacum , Oryza sativa (L.), Poncirus trifoliata (L.) Raf., Zea mays (L.), and Glycine max ( Lurin et al, 1996 ; Diedhiou and Golldack, 2006 ; Lv et al, 2009 ; Wang et al, 2015 ; Wei et al, 2015 ). Plants CLC proteins play important roles in turgor maintenance, stomatal movement, ion homeostasis, as well as enhancing drought and salt tolerance, and increasing nitrate accumulation ( Wei et al, 2015 ; Zhang et al, 2018 ; Liu C. et al, 2020 ).…”
Section: Introductionmentioning
confidence: 99%
“…CLC genes participate in Cl – and NO 3 – transport, are involved in response to salt stress, and are related to the efficiency of nitrogen use in plants ( Liao et al, 2018 ; Liu et al, 2020 ; Subba et al, 2020 ). Therefore, differences in CLC expression in vegetative tissues of P. × sibirica could be of interest in terms of determination of the possible role of sex in adaptation to particular environments.…”
Section: Discussionmentioning
confidence: 99%